A Correlation Between Education And Family’s Support To Life Quality In Breast Cancer Patients Undergoing Chemotherapy At Rsud Dr. M. Yunus Bengkulu In 2024 - Ramadanti, Nopita Dwi; Handayani, Tita Septi; Pebriani, Emi (Utami Publisher, 2025)
Breast cancer is one of the most common types of cancer in the world. In Asia, Indonesia is ranked second after India, with 66,271 new cases and 22,598 deaths in 2020. At RSUD Dr. M. Yunus Bengkulu, the number of patients with breast cancer who underwent chemotherapy was 138 people. The method used was analytic descriptive research design with cross sectional design with a sample of 57 patients undergoing chemotherapy in the Chemotherapy Room of Dr. M. Yunus Hospital Bengkulu. Data were collected through questionnaires and analyzed using the chi-square test. The results of the test analysis showed that there was no significant correlation between education level and quality of life of patients with a p-value of 0.078 (p> 0.05). There is a significant correlation between family support and patient quality of life with a p-value of 0.031 (p < 0.05). Patients who receive high family support have a better quality of life compared to patients who receive low family support. It is recommended that health workers prioritize programs that strengthen the role of families in supporting patients. Education and training that focuses on increasing family involvement and understanding of patient needs is very important to implement.